Patient satisfaction with directly observed treatment and multidrug-resistant tuberculosis injection administration by lay health workers in rural Eswatini - Ernest Peresu; Christo J Heunis; Gladys N Kigozi; Diana De Grave (AOSIS, 2020)
Background: The human resources for health crisis in rural Eswatini led to a novel community-based multidrug-resistant tuberculosis (MDR-TB) treatment strategy based on task-shifting, that is delegation of directly observed treatment (DOT) and administration of MDR-TB injections, traditionally restricted to professional nurses, to lay community treatment supporters (CTSs). Aim: This study assessed the level of patient satisfaction with receiving community-based MDR-TB care from a CTS. Setting: The study was conducted at three MDR-TB-treating facilities in the mostly rural Shiselweni region. Methods: A cross-sectional survey of a purposive sample of 78 patients receiving DOT and intramuscular MDR-TB injections from CTSs was carried out in 2017. Descriptive statistics and regressions were calculated. Results: A high overall general patient satisfaction score for receiving community-based MDR-TB care from a CTS was observed. Adherence counselling, confidentiality, provider selection and treatment costs significantly (p 0.05) influenced satisfaction. A large majority (n = 62; 79.5%) of patients indicated that they would likely recommend their significant others to receive MDR-TB care from a CTS. Respondents identified the need to provide CTSs with adequate training, regular supervision and sufficient incentives and also to broaden the scope of their services. Conclusion: This study observed that task-shifting of DOT and MDR-TB injection administration to CTSs was supported from a patient perspective. However, adherence counselling, confidentiality, provider selection and treatment costs should be taken into account in community-based MDR-TB care programming. Further to the patients, community-based tuberculosis care could be enhanced by improving CTSs' training, supervision and incentives, and broadening the scope of their services.